6.25 Problems 2401 to 2500

Table 6.49: Main lookup table sequentially arranged

#

ODE

Mathematica

Maple

2401

\[ {}t^{2} y^{\prime \prime }-t y^{\prime }+y = 0 \]

2402

\[ {}y^{\prime \prime }+y = \sec \left (t \right ) \]

2403

\[ {}y^{\prime \prime }-4 y^{\prime }+4 y = t \,{\mathrm e}^{2 t} \]

2404

\[ {}2 y^{\prime \prime }-3 y^{\prime }+y = \left (t^{2}+1\right ) {\mathrm e}^{t} \]

2405

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = t \,{\mathrm e}^{3 t}+1 \]

2406

\[ {}3 y^{\prime \prime }+4 y^{\prime }+y = \sin \left (t \right ) {\mathrm e}^{-t} \]

2407

\[ {}y^{\prime \prime }+4 y^{\prime }+4 y = t^{{5}/{2}} {\mathrm e}^{-2 t} \]

2408

\[ {}y^{\prime \prime }-3 y^{\prime }+2 y = \sqrt {t +1} \]

2409

\[ {}y^{\prime \prime }-y = f \left (t \right ) \]

2410

\[ {}y^{\prime \prime }+\frac {t^{2} y}{4} = f \cos \left (t \right ) \]

2411

\[ {}y^{\prime \prime }-\frac {2 t y^{\prime }}{t^{2}+1}+\frac {2 y}{t^{2}+1} = t^{2}+1 \]

2412

\[ {}m y^{\prime \prime }+c y^{\prime }+k y = F_{0} \cos \left (\omega t \right ) \]

2413

\[ {}y^{\prime \prime }+t y^{\prime }+y = 0 \]

2414

\[ {}y^{\prime \prime }-t y = 0 \]

2415

\[ {}\left (t^{2}+2\right ) y^{\prime \prime }-t y^{\prime }-3 y = 0 \]

2416

\[ {}y^{\prime \prime }-t^{3} y = 0 \]

2417

\[ {}t \left (2-t \right ) y^{\prime \prime }-6 \left (t -1\right ) y^{\prime }-4 y = 0 \]

2418

\[ {}y^{\prime \prime }+t^{2} y = 0 \]

2419

\[ {}y^{\prime \prime }-t^{3} y = 0 \]

2420

\[ {}y^{\prime \prime }+\left (t^{2}+2 t +1\right ) y^{\prime }-\left (4+4 t \right ) y = 0 \]

2421

\[ {}y^{\prime \prime }-2 t y^{\prime }+\lambda y = 0 \]

2422

\[ {}\left (-t^{2}+1\right ) y^{\prime \prime }-2 t y^{\prime }+\alpha \left (\alpha +1\right ) y = 0 \]

2423

\[ {}\left (-t^{2}+1\right ) y^{\prime \prime }-t y^{\prime }+\alpha ^{2} y = 0 \]

2424

\[ {}y^{\prime \prime }+t^{3} y^{\prime }+3 t^{2} y = 0 \]

2425

\[ {}y^{\prime \prime }+t^{3} y^{\prime }+3 t^{2} y = 0 \]

2426

\[ {}\left (1-t \right ) y^{\prime \prime }+t y^{\prime }+y = 0 \]

2427

\[ {}y^{\prime \prime }+y^{\prime }+t y = 0 \]

2428

\[ {}y^{\prime \prime }+t y^{\prime }+{\mathrm e}^{t} y = 0 \]

2429

\[ {}y^{\prime \prime }+y^{\prime }+{\mathrm e}^{t} y = 0 \]

2430

\[ {}y^{\prime \prime }+y^{\prime }+{\mathrm e}^{-t} y = 0 \]

2431

\[ {}t^{2} y^{\prime \prime }-5 t y^{\prime }+9 y = 0 \]

2432

\[ {}t^{2} y^{\prime \prime }+5 t y^{\prime }-5 y = 0 \]

2433

\[ {}2 t^{2} y^{\prime \prime }+3 t y^{\prime }-y = 0 \]

2434

\[ {}\left (t -1\right )^{2} y^{\prime \prime }-2 \left (t -1\right ) y^{\prime }+2 y = 0 \]

2435

\[ {}t^{2} y^{\prime \prime }+3 t y^{\prime }+y = 0 \]

2436

\[ {}t^{2} y^{\prime \prime }-t y^{\prime }+y = 0 \]

2437

\[ {}\left (t -2\right )^{2} y^{\prime \prime }+5 \left (t -2\right ) y^{\prime }+4 y = 0 \]

2438

\[ {}t^{2} y^{\prime \prime }+t y^{\prime }+y = 0 \]

2439

\[ {}t^{2} y^{\prime \prime }-t y^{\prime }+2 y = 0 \]

2440

\[ {}t^{2} y^{\prime \prime }-3 t y^{\prime }+4 y = 0 \]

2441

\[ {}t \left (t -2\right )^{2} y^{\prime \prime }+t y^{\prime }+y = 0 \]

2442

\[ {}t \left (t -2\right )^{2} y^{\prime \prime }+t y^{\prime }+y = 0 \]

2443

\[ {}\sin \left (t \right ) y^{\prime \prime }+\cos \left (t \right ) y^{\prime }+\frac {y}{t} = 0 \]

2444

\[ {}\left ({\mathrm e}^{t}-1\right ) y^{\prime \prime }+{\mathrm e}^{t} y^{\prime }+y = 0 \]

2445

\[ {}\left (-t^{2}+1\right ) y^{\prime \prime }+\frac {y^{\prime }}{\sin \left (t +1\right )}+y = 0 \]

2446

\[ {}t^{3} y^{\prime \prime }+\sin \left (t^{3}\right ) y^{\prime }+t y = 0 \]

2447

\[ {}2 t^{2} y^{\prime \prime }+3 t y^{\prime }-\left (t +1\right ) y = 0 \]

2448

\[ {}2 t y^{\prime \prime }+\left (1-2 t \right ) y^{\prime }-y = 0 \]

2449

\[ {}2 t y^{\prime \prime }+\left (t +1\right ) y^{\prime }-2 y = 0 \]

2450

\[ {}2 t^{2} y^{\prime \prime }-t y^{\prime }+\left (t +1\right ) y = 0 \]

2451

\[ {}4 t y^{\prime \prime }+3 y^{\prime }-3 y = 0 \]

2452

\[ {}2 t^{2} y^{\prime \prime }+\left (t^{2}-t \right ) y^{\prime }+y = 0 \]

2453

\[ {}t^{3} y^{\prime \prime }-t y^{\prime }-\left (t^{2}+\frac {5}{4}\right ) y = 0 \]

2454

\[ {}t^{2} y^{\prime \prime }+\left (-t^{2}+t \right ) y^{\prime }-y = 0 \]

2455

\[ {}t y^{\prime \prime }-\left (t^{2}+2\right ) y^{\prime }+t y = 0 \]

2456

\[ {}t^{2} y^{\prime \prime }+\left (-t^{2}+3 t \right ) y^{\prime }-t y = 0 \]

2457

\[ {}t^{2} y^{\prime \prime }+t \left (t +1\right ) y^{\prime }-y = 0 \]

2458

\[ {}t y^{\prime \prime }-\left (t +4\right ) y^{\prime }+2 y = 0 \]

2459

\[ {}t^{2} y^{\prime \prime }+\left (t^{2}-3 t \right ) y^{\prime }+3 y = 0 \]

2460

\[ {}t^{2} y^{\prime \prime }+t y^{\prime }-\left (t +1\right ) y = 0 \]

2461

\[ {}t y^{\prime \prime }+t y^{\prime }+2 y = 0 \]

2462

\[ {}t y^{\prime \prime }+\left (-t^{2}+1\right ) y^{\prime }+4 t y = 0 \]

2463

\[ {}t^{2} y^{\prime \prime }+t y^{\prime }+t^{2} y = 0 \]

2464

\[ {}t^{2} y^{\prime \prime }+t y^{\prime }+\left (t^{2}-v^{2}\right ) y = 0 \]

2465

\[ {}t y^{\prime \prime }+\left (1-t \right ) y^{\prime }+\lambda y = 0 \]

2466

\[ {}2 \sin \left (t \right ) y^{\prime \prime }+\left (1-t \right ) y^{\prime }-2 y = 0 \]

2467

\[ {}t^{2} y^{\prime \prime }+t y^{\prime }+\left (t +1\right ) y = 0 \]

2468

\[ {}t y^{\prime \prime }+y^{\prime }-4 y = 0 \]

2469

\[ {}t^{2} y^{\prime \prime }-t \left (t +1\right ) y^{\prime }+y = 0 \]

2470

\[ {}t^{2} y^{\prime \prime }+t y^{\prime }+\left (t^{2}-1\right ) y = 0 \]

2471

\[ {}t y^{\prime \prime }+3 y^{\prime }-3 y = 0 \]

2472

\[ {}\cos \left (t \right ) y+y^{\prime } = 0 \]

2473

\[ {}\sqrt {t}\, \sin \left (t \right ) y+y^{\prime } = 0 \]

2474

\[ {}\frac {2 t y}{t^{2}+1}+y^{\prime } = \frac {1}{t^{2}+1} \]

2475

\[ {}y^{\prime }+y = {\mathrm e}^{t} t \]

2476

\[ {}t^{2} y+y^{\prime } = 1 \]

2477

\[ {}t^{2} y+y^{\prime } = t^{2} \]

2478

\[ {}\frac {t y}{t^{2}+1}+y^{\prime } = 1-\frac {t^{3} y}{t^{4}+1} \]

2479

\[ {}\sqrt {t^{2}+1}\, y+y^{\prime } = 0 \]

2480

\[ {}\sqrt {t^{2}+1}\, y \,{\mathrm e}^{-t}+y^{\prime } = 0 \]

2481

\[ {}\sqrt {t^{2}+1}\, y \,{\mathrm e}^{-t}+y^{\prime } = 0 \]

2482

\[ {}y^{\prime }-2 t y = t \]

2483

\[ {}t y+y^{\prime } = t +1 \]

2484

\[ {}y^{\prime }+y = \frac {1}{t^{2}+1} \]

2485

\[ {}y^{\prime }-2 t y = 1 \]

2486

\[ {}t y+\left (t^{2}+1\right ) y^{\prime } = \left (t^{2}+1\right )^{{5}/{2}} \]

2487

\[ {}4 t y+\left (t^{2}+1\right ) y^{\prime } = t \]

2488

\[ {}y^{\prime }+y = \left \{\begin {array}{cc} 2 & 0\le t \le 1 \\ 0 & 1<t \end {array}\right . \]

2489

\[ {}\left (t^{2}+1\right ) y^{\prime } = 1+y^{2} \]

2490

\[ {}y^{\prime } = \left (t +1\right ) \left (y+1\right ) \]

2491

\[ {}y^{\prime } = 1-t +y^{2}-t y^{2} \]

2492

\[ {}y^{\prime } = {\mathrm e}^{3+t +y} \]

2493

\[ {}\cos \left (y\right ) \sin \left (t \right ) y^{\prime } = \cos \left (t \right ) \sin \left (y\right ) \]

2494

\[ {}t^{2} \left (1+y^{2}\right )+2 y y^{\prime } = 0 \]

2495

\[ {}y^{\prime } = \frac {2 t}{y+t^{2} y} \]

2496

\[ {}\sqrt {1+y^{2}}\, y^{\prime } = \frac {t y^{3}}{\sqrt {t^{2}+1}} \]

2497

\[ {}y^{\prime } = \frac {3 t^{2}+4 t +2}{-2+2 y} \]

2498

\[ {}\cos \left (y\right ) y^{\prime } = -\frac {t \sin \left (y\right )}{t^{2}+1} \]

2499

\[ {}y^{\prime } = k \left (a -y\right ) \left (b -y\right ) \]

2500

\[ {}3 t y^{\prime } = \cos \left (t \right ) y \]